Vietnam : 2019 Article IV Consultation; Press Release; Staff Report; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Vietnam highlights that gradual fiscal consolidation, strict limits on government guarantees and robust growth in recent years have led to declining government debt, expected to continue under current policies. But while there is some fiscal space, fiscal needs are large, for infrastructure, social spending and to deal with population aging. The tightening of credit growth continued in 2018; however, liquidity remained ample, aided by the strong balance of payments and tight fiscal policies. The State Bank of Vietnam has initiated plans to modernize its monetary framework with IMF technical support. The authorities' efforts to improve economic institutions and governance continue and the fight against grand corruption has resulted in significant sentences in recent high-profile cases. Improvements in transparency and statistical systems are underway, with support from the IMF and the Financial Action Task Force's Asia Pacific Group.